Consumers and consumption of agroecological products in the Members of the Network of Agroecological Markets of Bogotá, Region - RMABR - Chaparro Africano, Adriana María; Franco Chocue, Luz Magaly (Cooperativismo & Desarrollo, 2020)
The weakest sustainability indicators in the Agroecological Markets Network of Bogotá, Region, for 2016 and 2017, were the number of consumers and sales. Therefore, this research sought to characterize consumers and consumption in the RMABR, and then generate assertive communication, education and marketing strategies. A descriptive, mixed-focus investigation was carried out, for which a survey with twenty-six questions was applied through a Google form, between April 16 and May 17, 2018. The total sample was 149 consumers ( 80% reliability, 5% error). The analysis of the results was carried out using descriptive statistics and comparison with other studies. The main motivation for purchasing identified is health, while the reason for not buying is price, although there is a willingness to pay a 10% premium. The favorite products are cereals, fruits and vegetables, the preferred purchase frequencies are weekly and fortnightly, directly from producers and at fairs, with a majority range of less than 100,000 to 300,000 pesos. These studies are not common in agroecology, 16 similar studies were identified for organic products, but only one for agroecological ones.